Inkjet-printed gradient colorimetric indicators for monitoring fish freshness. (September 2021) - Luo, Xiaoyu; Ho, Ivan; Brankovan, Stevan; Lim, Loong-Tak
Highlights: Gradient colorimetric indicators were developed by piezoelectric inkjet printing. The indicators showed substantial color responses to stored fish fillets over time. The color responses were strongly correlated with volatile amine production. Inkjet-printed indicators can be potentially scaled up for intelligent packaging. Abstract: Gradient colorimetric indicators were developed by piezoelectric inkjet-printing, for monitoring the freshness of packaged fish fillets stored at 4 °C for 7 days. The pH-sensitive indicators involving three sulfonephthalein dyes were printed on inkjet photographic papers and applied as "intelligent" labels that were exposed to the headspace of the packages containing ocean perch, wild haddock or catfish fillets. The printability behaviours of the inks were investigated by determining their density, surface tension, and dynamic viscosity. The indicator labels exhibited striking color changes as the products spoiled during storage, which were correlated with total volatile basic nitrogen, trimethylamine, and dimethylamine levels in the package headspace. The indicators' color profiles observed at different storage times could be discriminated by principal component analysis. From partial least squares regression (R 2 > 0.95), the changes of volatile amine contents could be predicted from the indicators' color responses. This proof-of-concept study demonstrates that the innovative gradient indicator is promising for intelligent packaging of fishery and other perishable products.